Rock fall engineering - Wyllie, Duncan C. (CRC Press/Taylor & Francis Group, 2015)
"INTRODUCTION This book on rock fall engineering has arisen from an initial passing interest in the subject as the result of extensive project work on transportation projects in the mountainous area of North America. This interest developed into a mission to fully understand all aspects of rock fall behavior and the application of this behavior to the design and construction of protection structures. Lately this mission has evolved into an obsession to help develop improved methods of modeling rock falls and the design of more efficient and cost effective protection structures. As with my other two books, Foundations on Rock and Rock Slope Engineering, the intention of this book is to provide both the theory, and the application of the theory to design. In this book, this approach involves describing five case studies where the impacts are well defined, and then showing how trajectory calculations and impact mechanics can be applied to these actual rock fall conditions. It is hoped that the field data will be useful for calibration of computer rock fall simulation programs. In addition, a wide range of well proven rock fall protection measures are discussed. These discussions describe both design methods, and practical construction experience based on many projects in which the author has been involved. It is intended that users of this book will be both researchers working on the development of rock fall simulation, and practitioners working in the field of rock fall mitigation design and construction. My work on rock falls has benefited from my association over many years with practitioners involved with the design and construction of mitigation structure"--